Why We Don't Click: Interrogating the Relationship Between Viewing and Clicking in Social Media Contexts by Exploring the "Non-Click". Issue 6 (17th October 2020) - Ellison, Nicole B; Triệu, Penny; Schoenebeck, Sarita; Brewer, Robin; Israni, Aarti
Abstract: Motivated by work that characterizes view-based social media practices as "passive use, " contrasting it with more desirable, interactive "active use, " this study explores how social media users understand their viewing and clicking practices and the empirical relationship between them. Employing a combination of eye tracking, survey, and interview methods, our study (N = 42) investigates the non-click—instances where people intentionally and thoughtfully do not click on content they spend time viewing. Counterintuitively, we find no difference in viewing duration to clicked versus non-clicked Facebook content. We find that use motivations and Facebook feed content are significant predictors of click behavior but measures of overall use, such as network size or minutes of use per day, are not. Our interview data reveal three audience-related concerns that contribute to deliberate non-clicking and illustrate how non-clicked content contributes to social connectedness when imported into other channels. We discuss implications for researchers, users, and designers.